Clozapine‐induced agranulocytosis in Japan: Changes in leukocyte/neutrophil counts before and after discontinuation of clozapine. (18th May 2020) - Matsui, Kentaro; Ishibashi, Mikiko; Kawano, Masahiko; Oshibuchi, Hidehiro; Ishigooka, Jun; Nishimura, Katsuji; Inada, Ken
Abstract: Objective: To determine the prevalence, background factors, and progression of and recovery from clozapine‐induced agranulocytosis in Japan. Methods: Data on treatment‐resistant schizophrenia patients registered with the Clozaril Patient Monitoring Service (CPMS) between July 29, 2009 and January 20, 2016 were extracted. Patients with a neutrophil count <500/mm 3 were defined as having agranulocytosis, and those with a leukocyte count <3, 000/mm 3 or a neutrophil count <1, 500/mm 3 but not meeting the criteria for agranulocytosis were defined as having leukopenia/neutropenia. Results: Of 3, 746 patients, agranulocytosis and leukopenia/neutropenia were observed in 38 (1.0%) and 182 (4.9%) patients, respectively. Age was significantly higher in the agranulocytosis group ( p  < .001). Decreased leukocyte counts 1 week prior to discontinuation were observed only in the agranulocytosis group. The median number of days to recovery from agranulocytosis and leukopenia/neutropenia was 10 and 4, respectively, with more variation in the latter. Conclusions: Although some patients with leukopenia/neutropenia might carry less pathologic significance, the results of this study reconfirmed the importance of regular blood monitoring for preventing agranulocytosis.